2021
DOI: 10.1364/ol.419271
|View full text |Cite
|
Sign up to set email alerts
|

Topological rainbow based on graded topological photonic crystals

Abstract: Topological photonic crystal provides a robust platform for nanophotonic devices. However, few reports have been found to realize multiple frequency routing based on topological photonic states, which have restricted further applications in the field of nanophotonic devices. Here, for the first time, to the best of our knowledge, we propose an efficient method to realize a topological rainbow based on graded dielectric topological photonic crystals, which are constructed by changing the degree of lattice contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It should be emphasized that the similar topological rainbow phenomena have been studied in previous studies (Chen et al, 2019b;Zhang et al, 2021), but our ideas and studies are completely different from them. On the one hand, in ref.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…It should be emphasized that the similar topological rainbow phenomena have been studied in previous studies (Chen et al, 2019b;Zhang et al, 2021), but our ideas and studies are completely different from them. On the one hand, in ref.…”
Section: Discussionmentioning
confidence: 42%
“…On the other hand, in ref. Zhang et al (2021), the authors realized a rainbow based on graded dielectric photonic crystals, which are constructed by changing the degree of lattice contraction and expansion, so its physical mechanism of rainbow is completely distinguished from our study. Besides, this rainbow waveguide is composed of a dielectric material; thus, once its structure is fabricated, its properties cannot be adjusted, which greatly limits the application of rainbow waveguides.…”
Section: Discussionmentioning
confidence: 87%
“…The appearance of rainbow trapping offers a novel technique for frequency routing of slow light [1]. After the formation of the first theoretical work, many successive methods were presented to realize rainbow trapping, such as metamaterials [1,2], metasurfaces [3], plasmonic structures [4][5][6], phononic crystals in one-dimensional (1D) [7] and two-dimensional (2D) [8], and photonic crystals (PCs), in 1D [9], 2D [10,11] and three-dimensional (3D) [12]. Most of the mentioned methods depend on either metallic or dielectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired from the discovery of condensed quantum Hall effect, many studies have shown that topological states show essentially single-particle behavior of electrons and one can establish an analogy relationship with photon behaviors called topological photonic state (or topological one-way edge state) [4][5][6][7]. Topological one-way edge state provides a powerful platform for novel photonic devices with nontrivial functionalities and excellent performances, such as one-way waveguide [8][9][10][11][12], topological laser [13][14][15][16][17], rainbow trapping phenomenon [18][19][20][21], dispersionless slow light [22][23][24], topological fibre [25][26][27].…”
Section: Introductionmentioning
confidence: 99%